2019
DOI: 10.1111/joa.12972
|View full text |Cite
|
Sign up to set email alerts
|

Cell senescence, apoptosis and DNA damage cooperate in the remodeling processes accounting for heart morphogenesis

Abstract: During embryonic development, organ morphogenesis requires major tissue rearrangements that are tightly regulated at the genetic level. A large number of studies performed in recent decades assigned a central role to programmed cell death for such morphogenetic tissue rearrangements that often sculpt the shape of embryonic organs. However, accumulating evidence indicates that far from being the only factor responsible for sculpting organ morphology, programmed cell death is accompanied by other tissue remodeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 75 publications
4
14
0
Order By: Relevance
“…During eye development, cell senescence identified by specific SAβ-gal labeling, p21 gene expression and proliferation arrest, has been reported in differentiating neurons and photoreceptors of the developing retina (de Mera-Rodríguez et al, 2019). Similar findings were observed in the maturing ventricular myocardium of embryonic mice (Lorda-Diez et al, 2019). Whether these nondegenerative processes positive for SAβ-gal constitutes "true" cell senescence processes or reflects that distinct biological phenomena share mechanistic events remains to be clarified.…”
Section: Cell Senescence and Tendon Formation During Digit Developmentsupporting
confidence: 64%
See 1 more Smart Citation
“…During eye development, cell senescence identified by specific SAβ-gal labeling, p21 gene expression and proliferation arrest, has been reported in differentiating neurons and photoreceptors of the developing retina (de Mera-Rodríguez et al, 2019). Similar findings were observed in the maturing ventricular myocardium of embryonic mice (Lorda-Diez et al, 2019). Whether these nondegenerative processes positive for SAβ-gal constitutes "true" cell senescence processes or reflects that distinct biological phenomena share mechanistic events remains to be clarified.…”
Section: Cell Senescence and Tendon Formation During Digit Developmentsupporting
confidence: 64%
“…Consistent with the senescence nature of this morphogenetic process cell cycle arrest and overexpression of p21, p63, p73, and the Btg/Tob tumor suppressor gene family are precocious features of interdigit remodeling (Tone and Tanaka, 1997;Vasey et al, 2011;Lorda-Diez et al, 2015;Svandova et al, 2017). Furthermore, SAβ-gal histochemical staining is a very precise marker of INZs ( Figure 2B), and also identifies all other areas of embryonic cell death (Muñoz-Espín et al, 2013;Storer et al, 2013;Lorda-Diez et al, 2019). Remarkably, the pattern of SAβgal is indistinguishable from the pattern of staining with vital dyes (Figures 2A,B) or with specific lysosomal markers, such as LysoTracker (Zucker and Rogers, 2019).…”
Section: Cell Senescence Is a Feature Of The Inzssupporting
confidence: 56%
“…Thus, intense SA-β-GAL staining is detected in degenerating structures such as the pronephros of fish ( Villiard et al, 2017 ) and amphibians ( Davaapil et al, 2017 ; Villiard et al, 2017 ), and in the mesonephros of birds ( Nacher et al, 2006 ) and mammals ( Muñoz-Espín et al, 2013 ; Da Silva-Álvarez et al, 2018 ). The pattern of cell death in the developing avian heart also strongly correlates with SA-β-GAL staining ( Lorda-Díez et al, 2019 ), as do areas of cell death in the somites, tail bud, and CNS ( Muñoz-Espín et al, 2013 ; Storer et al, 2013 ). In the case of the developing otic vesicle in the chicken, SA-β-GAL labeled cells are associated with areas of increased apoptosis ( Figures 1A–C ) ( Gibaja et al, 2019 ; Magariños et al, 2020 ).…”
Section: Sa-β-gal Staining In the Developing Embryomentioning
confidence: 94%
“…SA-β-GAL staining in whole-mount mammalian embryos clearly shows that abundant labeled cells accumulates in the developing limbs, nails, focal areas of the skin, the tip of the tail, heart, eye tissues, inner ear, olfactory epithelium, and the closing neural tube ( Muñoz-Espín et al, 2013 ; Storer et al, 2013 ; Zhao et al, 2018 ), with a staining pattern similar to that observed in whole-mount chicken embryos ( Figures 1A–C ) (cf. Storer et al, 2013 ; Lorda-Díez et al, 2015 , 2019 ; Gibaja et al, 2019 ). More recently ( Da Silva-Álvarez et al, 2020 ), putative senescent cells during zebrafish development have been characterized in detail by using SA-β-GAL staining in whole mounts, with the strong activity being detected in the yolk, cloaca, central nervous system (CNS), intestine, liver, pronephric ducts, and lens.…”
Section: Sa-β-gal Staining In the Developing Embryomentioning
confidence: 99%
“…In the mouse, senescent cells have been identified by expression of β-galactosidase, p21 and SASP factors in many tissues during specific time windows of fetal development (mesonephros, neural tube, gut endoderm, heart, and the developing limbs, etc.) (Munoz-Espin et al, 2013;Storer et al, 2013;Lorda-Diez et al, 2019). These cells emerge and are removed by macrophages in a tightly controlled manner, resulting in tissue remodeling and patterning.…”
Section: Senescence During Early Embryo Developmentmentioning
confidence: 99%